Analysis of Sustainability Leverage Factors and Development Opportunities for the Corn Industry in Dompu Regency, West Nusa Tenggara - Jinem, Suparmin; Mernawati; Zaini, Anas (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to analyze the levers of sustainability and opportunities for the development of the corn industry in Dompu Regency, West Nusa Tenggara. The method used is descriptive method, data collection using interviews and online questionnaires to 60 farmer respondents spread across the three main corn-producing districts and 6 experts. The results of the study show that the lever factors that play a role in increasing sustainability are the ecological dimension "Spatial suitability for planting corn" the economic dimension "market access" the social dimension "Number of farmer households growing corn compared to the previous year" and the policy and institutional dimension "Policies related to price government purchase”. Meanwhile, potential factors that have not been maximized and have development opportunities are the Ecological dimension "utilization of corn waste" the Economic dimension "access to capital" the social dimension "how often farmers receive assistance related to corn" and the policy and institutional dimension "Policies related to pesticides, seeds/seeds and fertilizer. Keywords: Corn, Levarenge Factor, Dompu, Sustainable